1987
DOI: 10.1099/00222615-24-4-315
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Pseudomonas aeruginosa cytotoxin and toxin A on human polymorphonuclear leukocytes

Abstract: Summary. After exposure to cytotoxin or toxin A of Pseudomonas aeruginosa, the ultrastructure of resting and phagocytosing human polymorphonuclear leukocytes (PMNL) and of cells of P . aeruginosa strain 1348A was studied by transmission (TEM) and scanning (SEM) electronmicroscopy, and by light microscopy (LM) after histochemical staining of cytoplasmic granules. Cytotoxin caused marked clumping and destruction of PMNL, pyknotic nuclear changes with bleb formation, and release of cytoplasmic granules; phagocyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Recent morphological evidence shows that the plant toxins ricin and abrin inflict typical apoptotic changes in lymphoid and intestinal tissue (19). Pseudomonas cytotoxin and exotoxin A also cause morphological changes that resemble programmed cell death (7). In parallel studies with U937 cells, we found that TNF, DTx, ricin, and Pseudomonas exotoxin A all induce DNA fragmentation, widespread membrane blebbing, and eventual cell lysis (M. P. Chang and B. J. Wisnieski, unpublished data).…”
Section: Discussionmentioning
confidence: 53%
“…Recent morphological evidence shows that the plant toxins ricin and abrin inflict typical apoptotic changes in lymphoid and intestinal tissue (19). Pseudomonas cytotoxin and exotoxin A also cause morphological changes that resemble programmed cell death (7). In parallel studies with U937 cells, we found that TNF, DTx, ricin, and Pseudomonas exotoxin A all induce DNA fragmentation, widespread membrane blebbing, and eventual cell lysis (M. P. Chang and B. J. Wisnieski, unpublished data).…”
Section: Discussionmentioning
confidence: 53%
“…Among enterics and pseudomonads, some species (especially P. aeruginosa) have been shown to be tissue invasive (9), elaborate extracellular leukotoxins (5,7,52) and hemolysins (10,50), suppress lymphocyte proliferation (32), inactivate complement components (62), inactivate plasma alpha-1 -proteinase inhibitor (43,47), degrade immunoglobulins TgG and TgA (17,43), kill fibroblasts (43), inhibit mammalian cell protein synthesis (31), degrade basement membrane laminin (25), release potent enterotoxins and endotoxins (9), and elaborate coUagenolytic (26,43) and other proteolytic enzymes (10,43,44).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of cell volume coincided with nuclear accumulation of ethidium homodimer-1 (see the video in the supplemental material). Lysis of neutrophils by PA99null at later times was likely due to other factors produced by P. aeruginosa that have been shown to kill neutrophils or have been hypothesized to have such activity (5,37). Ethidium homodimer-1 staining was not observed in uninfected cells (data not shown).…”
Section: Vol 76 2008 P Aeruginosa Induces Localized Immunosuppressmentioning
confidence: 91%